Mycophenolate Mofetil for a Flare Child Lupus Nephritis: A Case Reports - Gina Puspita; Desy Rusmawatiningtyas; Sumadiono (Archives of The Medicine and Case Reports, 2021)
Renal involvement is the most common complication of systemic lupus erythematosus (SLE) and is also an important predictor of patient mortality. The incidence of flares is estimated at 65% each year in patients with lupus nephritis. Therapy in lupus nephritis with flare also uses high doses of steroid agents and strong immunosuppression agents. Mycophenolate mofetil (MMF) as an immunosuppression agent tends to favor for flare in lupus nephritis. We describe a patient who had a flare in lupus nephritis that resolved with high-dose steroid and MMF. The combination of immunosuppression agents and high-dose corticosteroids is effective for the control of active diseases. Cyclophosphamide as the steroid-sparing agent was discontinued because of adverse effects as well as hematuria. Partial remission was later achieved and maintained with MMF and corticosteroid after five months of protocol treatment. Thus, MMF while maintaining the steroid dose may induce remission for this case.